1997
DOI: 10.1021/la9701135
|View full text |Cite
|
Sign up to set email alerts
|

Control of Molecular Arrangement in Langmuir−Blodgett Films of Chlorophyll a Prepared in Various Gas Phases Studied by Ultraviolet−Visible and Infrared Spectroscopies and Atomic Force Microscopy,

Abstract: Attenuated total reflection (ATR)/Fourier-transform infrared (FT-IR) spectra were measured for one-monolayer Langmuir−Blodgett (LB) films of chlorophyll a (Chl-a) fabricated in an argon (Ar) atmosphere. The frequencies of CO stretching bands and marker bands for the coordination number of the central Mg atom suggest that Chl-a takes a five-coordinated dimer in the films prepared in the Ar atmosphere. Ultraviolet−visible (UV−vis) as well as IR spectra were obtained for multilayer LB films of Chl-a prepared in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For several decades, LB films containing major chloroplast pigments have been proposed to serve as models of photosynthesis. In particular, LB films of chlorophyll a have received considerable interest as a model to investigate chloroplast thylakoid, the structural unit of photosynthesis. The central issue in photosynthesis is the process of light-induced charge separation whereby light energy is converted into chemical energy. Chlorophyll a is a principal pigment in this energy transduction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For several decades, LB films containing major chloroplast pigments have been proposed to serve as models of photosynthesis. In particular, LB films of chlorophyll a have received considerable interest as a model to investigate chloroplast thylakoid, the structural unit of photosynthesis. The central issue in photosynthesis is the process of light-induced charge separation whereby light energy is converted into chemical energy. Chlorophyll a is a principal pigment in this energy transduction .…”
Section: Introductionmentioning
confidence: 99%
“…Until now, there have been few studies of LB films containing natural pigments which are anchored and stabilized by a matrix of a strong polymer. Sato et al reported the morphological and molecular structure of LB films of chlorophyll a in detail, though the photoelectrochemical behavior of the films was not investigated. , To the contrary, Miyasaka et al reported the photoelectrochemical behavior of chlorophyll mixed monolayers, , though the matrix used was stearic acid or lecithin. Matsuura et al reported the fabrication of LB films of β-carotene, though a β-carotene monolayer was transferred onto only hydrophilic substrates and the fabrication technique was rather difficult …”
Section: Introductionmentioning
confidence: 99%